PENGARUH PERILAKU PEMIMPIN TERHADAP MOTIVASI KERJA, KEPUASAN KERJA DAN KINERJA GURU DAN PEGAWAI DI LINGKUNGAN UNIT SMA DWIJENDRA DENPASAR - Pramita Darmayanti, Ni Wayan; Supartha, Wayan Gede; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.05.TAHUN 2016, 2016)
Leadership plays an important role in an organization , the leader is the main driving force in the organization so that all of the goals , vision and mission of the organization can be achieved , to achieve all that organizations need to pay attention to the efforts that the work motivation of teachers and employees are motivated to work more optimally and providing all resources to the organization . So teachers and staff need to be supported by giving attention to the needs of teachers and staff . Job satisfaction of teachers and employees seen from the high level of perceived satisfaction in working condition , while the performance of teachers and staff , the increase of the existing competence is from generating optimal performance . The population in this study were all the teachers and staff of the Dwijendra high school unit Denpasar, the sampling method used is the census and the sample size of 60 people. Examiners research hypotheses using PLS with the data processing program . These results indicate d that: (1) the positive effect of behavior leader on work motivation. (2) the positive effect of behavior leader on job satisfaction. (3) the positive effect of behavior leader on performance. (4) work motivation positive effect on performance. (5) job satisfaction has positive influence on performance. The implication of this study were behavior leader, work motivation, job satisfaction, performance of teachers and staff need to be improved in order to increase the job satisfaction of teachers and staff of the Dwijendra high school unit Denpasar. If the increased satisfaction w ould be able to improve the performance of the teachers and staff of the high school Dwijendra Denpasar.
Keywords: Behavior leader, Work Motivation, Job Satisfaction, Performance